Diastereoselective intramolecular aldol ring closures of threonine derivatives leading to densely functionalised pyroglutamates related to oxazolomycin - Heaviside, E; Moloney, M; Thompson, A (Royal Society of Chemistry, 2014)
Intramolecular aldol reactions on oxazolidine templates derived from threonine may be used to generate libraries of densely functionalised pyroglutamates with a high level of diastereoselectivity; the oxazolidine precursors themselves are suitable for further direct manipulation by side chain alkylation, permitting rapid access to cyclised products with several points of chemical diversity. Although these systems may be considered to be structural mimics of the functionalised pyroglutamate portion of oxazolomycin, little antibacterial activity against S. aureus and E. coli was found. These systems may additionally have application as three-dimensional fragments for drug discovery and development.